An Integrative Program to Reduce Stigma in Primary Healthcare Workers Toward People With Diagnosis of Severe Mental Disorders: A Protocol for a Randomized Controlled Trial - Grandón, Pamela; Saldivia, Sandra; Vaccari, Pamela; Ramirez-Vielma, Raul; Victoriano, Víctor; Zambrano, Carlos; Ortiz, Camila; Cova, Felix (Frontiers in Psychiatry, 2019)
Background: People with severe mental disorders (SMDs) have higher disease and death rates than the general population. Stigma (negative attitudes and perceptions) contributes to limited access to health services and a lower quality of medical assistance in this population, and it is manifested as negative attitudes, social distance, and discrimination toward this social group. For these reasons, healthcare workers are a priority group for anti-stigma interventions. This study aims to assess the effectiveness of a program specifically designed to decrease negative attitudes and social distance and increase inclusive behaviors in healthcare workers toward people with SMD. Methods: The study will be a randomized clinical trial. A minimum of 210 healthcare workers from 11 primary care centers in the province of Concepción, Chile, will be randomly chosen to receive the program or be part of the control group. There will be a pre-, post-, and 4-months evaluation of social distance, attitudes, and behaviors of participants toward people with SMD using standardized scales such as the social distance scale, which is a scale of clinician attitude toward mental illness adapted from attitudes of clinicians toward mental illness, and self-reports. The intervention program will consist of education strategies, direct, and indirect contact with people diagnosed with SMD, and skill development. There will be six face-to-face sessions directly with the participants and two additional sessions with the directors of each healthcare center. The program will involve a facilitator who will be a healthcare professional and a co-facilitator who will be a person diagnosed with SMD. Discussion: This study will evaluate an intervention program especially designed to reduce stigma in healthcare workers toward people with SMD, a topic on which there is little background information, particularly in low- and middle-income countries. It is important to have interventions with proven effectiveness for this purpose to ensure equity in healthcare services. Trial Registration: This study was registered under ISRCTN.com (ISRCTN46464036).